Travel behaviour and perception of mode public transportation among users in Malaysia - Salim, Salman; ., Nurul Izzati; ., Jeo Amran; Che Manaf, Nor Syahidah; Mohd Azmy, Syakirul Azim (Penerbit UTHM, 2020)
Shared mobility can be defined as the transportations that are shared among users such as public transit (e.g. bus, commuter, LRT, MRT), taxis, bike sharing, car sharing, and e-hailing services (e.g. Grab) to obtain short-term access. Shared mobility sits within the broader phenomenon that has been termed as ‘sharing economy’, in which wide spread usage of emerging information and communications technology (ICT), particularly smartphones, enables new forms of market interactions that can enable both new services and improved efficiency in asset utilization [1, 2]. This scenario has given many benefits especially towards e-hailing services where the users can order a driver to pick up himself or herself at a designated area and send them to the destination that they want only using an application on smartphones. Other than that, it also gives a revolution of public transportation such as bus by purchasing the ticket through online system. This are the transformations and the trend changes from oldest system to further system.